Social-psychological characteristics adaptation of child institution social protection - Julia Udovenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
This article describes the process of adaptation as part of a multidisciplinary approach. The process of adaptation of the child in an institution of social protection on the basis of two related species adaptation, psychophysiological, social and psychological. Defined social-psychological characteristics of the process of adaptation of the child in an institution of social protection.
Keywords: adaptation; difficult life circumstances; institutions of social protection